GABA and glutamate in pediatric migraine. Issue 1 (January 2021) - Bell, Tiffany; Stokoe, Mehak; Khaira, Akashroop; Webb, Megan; Noel, Melanie; Amoozegar, Farnaz; Harris, Ashley D.
Abstract : Abstract: Migraine is one of the top 5 most prevalent childhood diseases; however, effective treatment strategies for pediatric migraine are limited. For example, standard adult pharmaceutical therapies are less effective in children and can carry undesirable side effects. To develop more effective treatments, improved knowledge of the biology underlying pediatric migraine is necessary. One theory is that migraine results from an imbalance in cortical excitability. Magnetic resonance spectroscopy (MRS) studies show changes in GABA and glutamate levels (the primary inhibitory and excitatory neurotransmitters in the brain, respectively) in multiple brain regions in adults with migraine; however, they have yet to be assessed in children with migraine. Using MRS and GABA-edited MRS, we show that children (7-13 years) with migraine and aura had significantly lower glutamate levels in the visual cortex compared to controls, the opposite to results seen in adults. In addition, we found significant correlations between metabolite levels and migraine characteristics; higher GABA levels were associated with higher migraine burden. We also found that higher glutamate in the thalamus and higher GABA/Glx ratios in the sensorimotor cortex were associated with duration since diagnosis, i.e., having migraines longer. Lower GABA levels in the sensorimotor cortex were associated with being closer to their next migraine attack. Together, this indicates that GABA and glutamate disturbances occur early in migraine pathophysiology and emphasizes that evidence from adults with migraine cannot be immediately translated to pediatric sufferers. This highlights the need for further mechanistic studies of migraine in children, to aid in development of more effective treatments. Abstract : Supplemental Digital Content is Available in the Text.Using magnetic resonance spectroscopy in vivo, we show GABA and glutamate alterations in children aged 7 to 13 years with migraine, which are associated with migraine characteristics.